I Love Cats - Catherine Matthias (USA Childrens Press Chicago, 1983)
A fun and engaging way for young children to figure out concepts and solving problems on his or her own. Rookie Readers (Ages 5-7) have provided entertaining, high-quality introductions to reading for more than a generation. Each title features full-color, often hilarious illustrations and engaging stories that always involve a young child figuring out concepts or solving problems on his or her own. Other animals may be very nice, but cats are the best ones to love.
Keywords: F&P - IR - E1 -- F&P - IR - E1